Modified Gegen Qinlian Decoction Regulates Treg/Th17 Balance to Ameliorate DSS-Induced Acute Experimental Colitis in Mice by Altering the Gut Microbiota - Wang, Yifan; Zhang, Jiaqi; Xu, Lin; Ma, Jing; Lu, Mengxiong; Ma, Jinxin; Liu, Zhihong; Wang, Fengyun; Tang, Xudong (Frontiers in Pharmacology, 2021)
Inflammatory bowel disease (IBD) is characterized by chronic pathology associated with extensive intestinal microbial dysregulation and intestinal inflammation. Thus, efforts are underway to manipulate the gut microbiome to improve inflammatory pathology. Gegen Qinlian decoction (GQD), a traditional Chinese medicine prescription, has been widely utilized for treating diarrhea and ulcerative colitis (UC) for thousands of years. However, the underlying mechanism of its efficacy and whether its protective effect against colitis is mediated by the gut microbiota are poorly understood. In the present study, our data demonstrated that modified GQD (MGQD) administration significantly improved the pathological phenotypes and colonic inflammation challenged by DSS in mice, which were specifically manifested as reduced loss of body weight, shortening of colon length, DAI score, histological score and suppressed inflammatory response. 16S rRNA sequencing and targeted metabonomics analysis showed that MQGD altered the diversity and community landscape of the intestinal microbiota and the metabolic profiles. In particular, MQGD significantly boosted the abundance of the intestinal microbiota producing short-chain fatty acids (SCFAs), which are causally associated with promoting the development of Treg cells and suppressing the differentiation of pro-inflammatory Th17 cells. More importantly, transferring fecal microbiota from MGQD-treated or healthy controls exhibited equivalent alleviative effects on colitis mice. However, this protective effect could not be replicated in experiments of mice with depleted intestinal microbes through broad-spectrum antibiotic cocktails (ABX), further supporting the importance of SCFA-producing gut microbiota in the beneficial role of MGQD. In general, MGQD therapy has the potential to remodel the intestinal microbiome and reestablish immune homeostasis to ameliorate DSS-induced colitis.